2021
DOI: 10.3390/jcm10215211
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Assessment of the Quality of Life in Patients with Colorectal Endometriosis

Abstract: Morbidity and mortality alone are not comprehensive measures of evaluating the benefits of surgical interventions in endometriosis patients, thus, subjective patient-reported instruments are required. The 36-tem Short Form Survey (SF-36) is a Health-Related Quality of Life (HRQoL) instrument that has not been validated yet for women with endometriosis. The aims of this study are to evaluate the validity and reliability of the SF-36 in patients with colorectal endometriosis and to compare the HRQoL before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the pelvis, endometriosis can lead to deeper lesions affecting the bladder, rectum, sigmoid tract, rectovaginal septum, parametrium and/or uterosacral ligaments [5]. These lesions are commonly aggregated under deep infiltrating endometriosis (DIE) [5,6], which often requires extensive surgery leading to severe morbidity [7]. Several studies have now shown that transvaginal sonography (TVS) performed by an expert sonographer can be regarded as being an accurate method in defining DIE nodules and their extension, as magnetic resonance imaging (MRI) [5,8,9]; although, accurate diagnosis of nodules of the uterosacral ligaments and parametrium remains problematic [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the pelvis, endometriosis can lead to deeper lesions affecting the bladder, rectum, sigmoid tract, rectovaginal septum, parametrium and/or uterosacral ligaments [5]. These lesions are commonly aggregated under deep infiltrating endometriosis (DIE) [5,6], which often requires extensive surgery leading to severe morbidity [7]. Several studies have now shown that transvaginal sonography (TVS) performed by an expert sonographer can be regarded as being an accurate method in defining DIE nodules and their extension, as magnetic resonance imaging (MRI) [5,8,9]; although, accurate diagnosis of nodules of the uterosacral ligaments and parametrium remains problematic [5].…”
Section: Introductionmentioning
confidence: 99%
“…The lowest level of GIQLI points were reported from several disease entities such as 71.3 (49.5% of the maximum) in a cohort of fecal incontinence, 76.6 (53.2% of the maximum) in a cohort of patients with endometriosis, 56.2 (39% of the maximum) in a cohort of patients with irritable bowel syndrome (IBS), and 63 (43.8% of the maximum) in a cohort of patients with constipation [ 33 , 45 , 47 ]. It can be stated as a summary of these results that patients with benign colorectal diseases may suffer from a major reduction in quality of life during the course of the disease, which requires optimal care to improve their situation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, decreased scores reported on the subscales “role functioning”, “physical functioning”, and “fatigue symptom”, assessed by the EORTC-C30 questionnaire were key elements that caused the patient to discontinue cancer treatment. In addition, low social support was associated with a 2-fold increased risk for treatment discontinuation [ 71 , 72 ]. Furthermore, Stalmeier et al expose that in clinical practice, the treating physician tends to take ownership of therapeutic decisions, so that the patient does not question the physician about oncological decisions.…”
Section: Discussionmentioning
confidence: 99%